Is standing by your moral opinion a Western phenomenon?: a cross-cultural study on moral consistency - Ali Sarmad (2020)
Western theories on morality imply that being consistent in one´s moral beliefs, i.e. moral consistency, is a fundamental attribute of a moral person. In this study, it is argued that this kind of moral consistency can be counter-productive in some cultures, especially if demonstrated in social situation with ingroup members. When moral consistency entails confronting others with opposing opinions about moral issues, relationships with ingroup members may be seen at risk of being jeopardized in Eastern cultures that value interdependent and harmonious relations with others. In this case, moral consistency might be seen as a sign of arrogance, impurity and rebellion. In order to examine the hypothesis that there is cross-cultural variation in moral consistency, two empirical studies were conducted. A pilot study was conducted to identify specific issues that are considered to be equally moral and debatable between an Eastern and a Western culture. In the main study, participants´ attitude on moral and non-moral issues were assessed (in favor or against) and they were then instructed to imagine different social situations in which either outgroup or ingroup members would have opposing opinions. Hence, the experiment consisted of a 2 (culture: West vs. East) x 3 (issue: death penalty, torturing terrorism suspects to extract information, drinking orange juice at breakfast) x 3 (social situation: strangers, friends, family) mixed design with issue and social situation being within-subject factors. The results partially confirmed the hypothesis by showing that Westerners are overall more consistent in expressing their moral opinions than Indian participants. This has important implications for intercultural interactions, because this cultural difference in context-independent and context-dependent moral functioning can create serious misunderstandings in intercultural encounters.